The Importance of a Business Plan when Planning a Lexicographical Project - Alberts, Mariëtta (Lexikos, 1999)
This paper deals with the importance of a business plan when planning a lexicographical project. A business plan is an aspect of a lexicographical process most lexicographers would like to ignore. It is, however, an important step towards the establishment of a dictionary project. The compilation of a dictionary is a time-consuming process and a costly business, and proper planning is of the utmost importance, whether a dictionary project is undertaken by an individual or by a team of lexicographers. Therefore a business plan is the ideal tool for proper planning before embarking on a lexicographical project. It also gives stakeholders an indication of the scope of the envisaged lexicographical project. Financiers require a business plan to authorise the financing of a project, and this also applies to a lexicographical project. This paper deals with the importance of and reasons for a business plan. It also covers aspects such as drawing up a business plan as well as its contextual requirements. Keywords: action plan; business plan; collaborators; critical success factor; empirical survey; end user; financier; goal; human resources; key service; key uncertainty; knowledge transfer; lexicographical practice; lexicography unit; mission; needs assessment; objective; opportunity; organisational structure; risk; situation analysis; stakeholder; strategy; vision